2023
DOI: 10.2147/dmso.s405554
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Clinical Significance of Serum 25-Hydroxyvitamin D3 and Vasohibin-1 (VASH-1) Levels in Patients with Diabetic Nephropathy and Different Renal Injuries

Abstract: Objective We investigate the relationship between the changes of serum 25-hydroxyvitamin D3 (25(OH)D3) and vasohibin-1 (VASH-1) and renal function injury in patients with type 2 diabetic nephropathy. Methods In this study, 143 patients with diabetic nephropathy (DN) were selected as DN group, and 80 patients with type 2 diabetes mellitus were selected as T2DM group. The serum 25 (OH) D3, VASH-1, blood glucose index, inflammation index and renal function index were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…VASH-1, an endogenous negative feedback regulator of angiogenesis, plays a role in regulating various factors to inhibit angiogenesis. It has been reported in diseases such as atherosclerosis, diabetic nephropathy, and pulmonary fibrosis [18,33,34]. Notably, studies have suggested that, apart from its association with the progressive decline in renal function [4], VASH-1 might potentially exert protective effects through negative feedback in renal diseases [18,35].…”
Section: Discussionmentioning
confidence: 99%
“…VASH-1, an endogenous negative feedback regulator of angiogenesis, plays a role in regulating various factors to inhibit angiogenesis. It has been reported in diseases such as atherosclerosis, diabetic nephropathy, and pulmonary fibrosis [18,33,34]. Notably, studies have suggested that, apart from its association with the progressive decline in renal function [4], VASH-1 might potentially exert protective effects through negative feedback in renal diseases [18,35].…”
Section: Discussionmentioning
confidence: 99%